FROM BIOLOGICAL COLONIZATION TO THE SOIL AND CRUST FORMATION: THE ROLE OF CYANOBACTERIA AND SMALL ANIMALS IN A KARSTIC LANDSCAPE, NORTH OF MINAS GERAIS STATE, BRAZIL - Mendonça de Oliveira, Araceli; Pereira, Thiago Torres Costa; Soares de Oliveira, Fábio; Ferreira de Freitas, Diana (REVISTA GEOGRÁFICA ACADÊMICA, 2023)
The susceptibility of limestones to biological colonization can be a significant role in the development of karst relief, since the microbial biofilms formation and exopolymeric compounds produced by different metabolic activities, and can influence the dissolution processes and precipitation of minerals, boosting specific transformations at karst. Study about biological performance in limestone outcrops in Brazil are still scarce, so it was aimed to analyze the role of the cyanobacteria and small animals (rodents and marsupials) in the superficial transformation of limestones and soil formation in the North of Minas Gerais state. Thus, the methods used were the total organic carbon content with fractionation of humic substances, potential acidity, and micromorphological and microchemistry characterization. The results showed a low recovery of total organic carbon, with a predominance of humin, followed by humic and fulvic acids. The potential acidity presented values classified as very low to very high, and the micromorphological and microchemistry images showed some specific features of the limestone. The conclusion is that the cyanobacteria, rodents and marsupials are part of the karst relief evolution, and possibly the effects of their colonization were able to promote the formation of biofilms, which through complex metabolic interactions, stimulated the processes of biokarstification, favoring the surface transformations at limestone and the soil and crust formation, that contribute to the karst relief